Psychological distress in North America during COVID-19: The role of pandemic-related stressors. (February 2021) - Zheng, Jason; Morstead, Talia; Sin, Nancy; Klaiber, Patrick; Umberson, Debra; Kamble, Shanmukh; DeLongis, Anita
Abstract: Rationale: The COVID-19 pandemic has wreaked havoc on lives around the globe. In addition to the primary threat of infection, widespread secondary stressors associated with the pandemic have included social isolation, financial insecurity, resource scarcity, and occupational difficulties. Objective: The current study examined the impact of these disruptions on psychological distress during the initial adjustment phase to the pandemic in North America. Method: A sample of 2463 residents of the US and Canada completed both baseline and follow-up surveys across several weeks between March and May 2020. Results: Those participants perceiving stress related to higher levels of personal threat to health and to the well-being of family members at baseline reported higher levels of depressive symptoms at follow-up, even after controlling for baseline depressive symptoms. In addition, pandemic-related secondary stressors (social isolation, financial insecurity, occupational difficulty, and resource scarcity) were all independently associated with depressive symptoms at follow-up, controlling for both baseline depression and perceived health threats. The results were robust and held up after controlling for demographic factors. Women, young adults, and those who reported lower income were all at higher risk for subsequent depressive symptoms. Conclusion: Findings from the present study can help to identify key groups at risk for mental health problems during the pandemic, and indicate actionable areas for targeted intervention. Highlights: Examines mental health during early stages of COVID-19 pandemic in North America. COVID threat to oneself and loved ones was associated with increased depression. Secondary pandemic-related stressors were also associated with depression risk. Women, young adulthood, and low income were also risk factors for depression.